(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The objective of this study was to analyze the sequence of different fragments of the thyroperoxidase (TPO) gene from a cat diagnosed with congenital hypothyroidism (CH). Materials and Methods: The feline was diagnosed due to high serum concentrations of thyroid-stimulating hormone and low T4. The analysis of sequences containing mutations in the TPO gene from dogs with CH allowed for the prediction of mutation sites within the gene in an affected cat. In addition, the design of a polymerase chain reaction-based test allowed the amplification and sequencing of these gene segments. In addition, after the death of the patient, a necropsy and histopathology were performed, looking for macroscopic and microscopic alterations of affected organs. Results: The necropsy examination showed megacolon, cardiac concentric left ventricular hypertrophy, and bilateral enlargement of the thyroid gland. The histopathology of the thyroid showed follicular hypoplasia and low colloid production. gDNA analysis allowed the detection of mutation in the TPO gene, which corresponded to one transition in the nucleotide 12.542 (A > G) and heterozygous variations located in the nucleotide 14.627 (G/A) and in the nucleotide 30.713 (G/C). Conclusion: Due to the presence of these polymorphisms, it is suspected that one monoallelic expression of mutant alleles is present. More studies that allow an understanding of the role of the heterozygous in this pathology are required, as well as the role of gene mutations related to CH in cats. On the other hand, the data from the present study serve as the base for the development of a molecular test that allows a fast and accurate diagnosis of HC in cats. J. Adv. Vet. Anim. Res., 11(4): 1030–1036, December 2024 http://doi.org/10.5455/javar.2024.k854